The Energy and Gross Domestic Product Causality Nexus in Latin America 1900-2010 - Leiva, Benjamin; Rubio-Varas, Mar (International Journal of Energy Economics and Policy, 2019)
A better understanding of the relationship between energy consumption and economic growth is important for the less developed regions of the world such as Africa or Latin America, which future might be compromised by the imposition of the transition to a lower carbon economy. Studies on the energy-GDP nexus for Latin America have been few and bounded to short periods. We fill this gap by searching for causal paths between energy and GDP for 20 Latin American countries using a newly compiled dataset spanning the twentieth century. Our main identification strategy is based on super exogeneity, which we complement with Granger tests, Toda and Yamamoto and enrich by controlling for structural breaks and the False Discovery Rate. The results highlight the inexistence of a homogeneous relation between energy and GDP in highly heterogeneous spatial and temporal dimensions, and thus the need to enhance our theoretical understanding of this relation. The policy implication is that designing and implementing energy policies coming from a single methodological approach and based on aggregated results should be avoided. Keywords: Energy, Gross Domestic Product, causality JEL Classifications: Q2, Q4 DOI: https://doi.org/10.32479/ijeep.8670